PERBEDAAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE DAN MODEL PEMBELAJARAN KONSIDERASI TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PADA ASPEK AFEKTIF (STUDI PADA SISWA KELAS VII SMP NEGERI 16 SURAKARTA TAHUN AJARAN 2011/2012) - Anwar, Chairul (Prodi PPKn FKIP UNS, 2013)
The objective of research is to find out the different of Value Clarification Technique and Consideration learning models on civic education learning achievement in affective aspect in the VII Graders of SMP Negeri 16 Surakarta in the School Year of 2011/2012 in basic competency of applying norms, habits, customs, and regulation prevailing in society, nation, and country life. This study was a quantitative research. The method used was an experimental method. The population of research was all VII graders of SMP Negeri 16 Surakarta in the School Year of 2011/2012, consisting of 160 students. The sample consisted of 56 students taken using a simple random sampling technique. Technique of collecting data used was attitudinal scale questionnaire. Technique of analyzing data used was a one-way anova analysis technique. Considering the result of research conducted, it could be concluded that there was a different of value clarification technique learning model from that of consideration learning model on civic education learning achievement in affective aspect in the VII Graders of SMP Negeri 16 Surakarta in the School Year of 2011/2012 in basic competency of applying norms, habits, customs, and regulation prevailing in society, nation, and country life. It could be seen from the result of calculation using one-way anova analysis technique indicating that the learning achievement of civic education in affective aspect obtained Fstatistic = 5.70 > Ftable = 4.02 at significance level of 5%.